The impact of HIV on the prevalence of asthma in Uganda: a general population survey - Kirenga, Bruce J. (Respir Res, 2018)
BACKGROUND: HIV and asthma are highly prevalent diseases in Africa but few studies have assessed the impact of HIV on asthma prevalence in high HIV burden settings. The objective of this analysis was to compare the prevalence of asthma among persons living with HIV (PLHIV) and those without HIV participating in the Uganda National Asthma Survey (UNAS). METHODS: UNAS was a population-based survey of persons aged ≥12 years. Asthma was diagnosed based on either self-reported current wheeze concurrently or within the prior 12 months; physician diagnosis; or use of asthma medication. HIV was defined based on confidential self-report. We used Poisson regression with robust standard errors to estimate asthma prevalence and the prevalence ratio (PR) for HIV and asthma. RESULTS: Of 3416 participants, 2067 (60.5%) knew their HIV status and 103 (5.0%) were PLHIV. Asthma prevalence was 15.5% among PLHIV and 9.1% among those without HIV, PR 1.72, (95%CI 1.07–2.75, p = 0.025). HIV modified the association of asthma with the following factors, PLHIV vs. not PLHIV: tobacco smoking (12% vs. 8%, p = < 0.001), biomass use (11% vs. 7%, p = < 0.001), allergy (17% vs. 11%, p = < 0.001), family history of asthma (17% vs. 11%, p = < 0.001), and prior TB treatment (15% vs. 10%, p = < 0.001). CONCLUSION: In Uganda the prevalence of asthma is higher in PLHIV than in those without HIV, and HIV interacts synergistically with other known asthma risk factors. Additional studies should explore the mechanisms underlying these associations. Clinicians should consider asthma as a possible diagnosis in PLHIV presenting with respiratory symptoms.